TI_GERICHTE 12.2006.59 vom 6. März 2006 , ritiro dell'opposizione al PE - ACB provvisorio - azione di inesistenza del debito ex art. 85a - TI Tribunale d'appello (2006)
ritiro dell'opposizione al PE - ACB provvisorio - azione di inesistenza del debito ex art. 85a